Rheoencephalography: A non-invasive method for neuromonitoring - Szabo Sandor; Totka Zsolt; Nagy-Bozsoky Jozsef; Pinter Istvan; Bagany Mihaly; Bodo Michael (Journal of Electrical Bioimpedance)
In neurocritical care, the gold standard method is intracranial pressure (ICP) monitoring for the patient's lifesaving. Since it is an invasive method, it is desirable to use an alternative, noninvasive technique. The computerized real-time invasive cerebral blood flow (CBF) autoregulation (AR) monitoring calculates the status of CBF AR, called the pressure reactivity index (PRx). Studies documented that the electrical impedance of the head (Rheoencephalography – REG) can detect the status of CBF AR (REGx) and ICP noninvasively. We aimed to test REG to reflect ICP and CBF AR.